Mechanisms of the adaptive reactions development inthe students’ body - Gumenyuk, Sergiy; Hulka, Olha; Slozanska, Hanna; Gorbatiuk, Roman; Ladyka, Petro; Ognysta, Kateryna; Hrubar, Iryna (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The article substantiates the importance of the mechanisms of adaptive reactions, which includes various functionally related subsystems. Aim of Study. The aim of the article is analysis of psychophysiological indicators, central hemodynamics and heart rate variability of students’ organisms at the first year of study. Material and Methods. Contingent: students of University. The average age 17.5 ± 0.6 years. Methods for studying the properties of attention (tables Anfimov, Schulte), short-term arbitrary visual memory; 5-minute heart rate variability (HRV) records. Results. It is established that differences in mental functions are due to the specifics of educational process. High level of MVB, HR, SDNN and LF/ HF (р ≤ 0.05), in group I indicates increased hemodynamics and sympathicotonia. In the group ІІ indicators point to optimal level of central hemodynamics and activation of the sympathetic link. Group III smallest LF/HF (р ≤ 0.05) and normal hemodynamic characteristic. Group IV: lowest VLF and VLF%, the highest LF% and VEI – it’s may be the result of reduced ergotropic resources under stress. Conclusions. It is proposed to evaluate the mechanisms of adaptive reactions development: optimal, compensatory, decompensatory, overstrain.
Keywords: students; heart rate variability; central; hemodynamics; psychophysiological indicators; functional; systems; organism